2021
DOI: 10.21037/jtd-21-1801
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multi-groove silicone drains in single-port video-assisted thoracoscopic lung cancer surgery and their effect on C-reactive protein: a single-center experience

Abstract: Background: The purpose of this study was to systematically evaluate the effectiveness and safety of a multi-groove silicone drain in single-port video-assisted thoracoscopic lung cancer surgery and its effect on postoperative serum C-reactive protein (CRP) levels. Methods: We retrospectively analyzed 122 surgical cases who underwent standard lobectomy and lymph node dissection for primary lung cancer between May 2020 and December 2020. A total of 62 patients received 19-F multi-groove silicone drains (experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the field of segmentectomy for early-stage NSCLC, the more traditional surgical method is the three-port method, including the observation port, the main operating port, and the auxiliary operating port [ 4 , 5 ]. Although this traditional surgical method had become more and more mature, but massive scholars have found that there were some defects in three-port thoracoscopic surgery, such as numbness or dyskinesia at the distal end of the chest wall, and pain in the auxiliary operating port of the back [ 6 , 7 ]. So, the single-port thoracoscopic technique came into being, and it was also a major breakthrough in the minimally invasive technique of thoracic surgery in recent years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of segmentectomy for early-stage NSCLC, the more traditional surgical method is the three-port method, including the observation port, the main operating port, and the auxiliary operating port [ 4 , 5 ]. Although this traditional surgical method had become more and more mature, but massive scholars have found that there were some defects in three-port thoracoscopic surgery, such as numbness or dyskinesia at the distal end of the chest wall, and pain in the auxiliary operating port of the back [ 6 , 7 ]. So, the single-port thoracoscopic technique came into being, and it was also a major breakthrough in the minimally invasive technique of thoracic surgery in recent years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the serious air pollution and the gradual deterioration of the environment, the incidence of various lung diseases is on the rise, among which lung cancer has become one of the cancers with the highest incidence [ 4 ]. Data from the National Cancer Center showed that in 2020, the number of new lung cancer cases in China will reach 816,000, accounting for 17.9% of all cancers [ 5 ]. That is an average of 16 people getting sick every 10 minutes.…”
Section: Introductionmentioning
confidence: 99%